1999
DOI: 10.1046/j.1469-8137.1999.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

The dendrochronological potential of modern yew (Taxus baccata) with special reference to yew from Hampton Court Palace, UK

Abstract: Modern yew (Taxus baccata) is demonstrated to have considerable potential for dendrochronological use. A replicated 303 yr chronology has been formed from Hampton Court Palace yew and cross-matches well with a number of different tree species, including oak. Growth is positively correlated with rainfall but inversely related to late summer temperature. Range limits and present and prehistoric sources of yew are also briefly discussed, highlighting the future potential of yew to become the third major tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In particular, two study areas (MOR and FEM) are occupied by yew trees, both isolated and in groups with remarkable size as either stem diameter or total height (for a comparison of yew dimensions see also Rikhari et al 1998). The biggest yew individuals we encountered had flat crown tops, either because of truncation or dieback, and they also had hollow stems, as typical of the species (Moir 1999). Besides natural senescence, it is possible that these morphological characters have been selectively enhanced by past logging, which for economic reasons concentrated on individuals with regular crown and solid trunk.…”
Section: Stand Structure and Regenerationmentioning
confidence: 89%
“…In particular, two study areas (MOR and FEM) are occupied by yew trees, both isolated and in groups with remarkable size as either stem diameter or total height (for a comparison of yew dimensions see also Rikhari et al 1998). The biggest yew individuals we encountered had flat crown tops, either because of truncation or dieback, and they also had hollow stems, as typical of the species (Moir 1999). Besides natural senescence, it is possible that these morphological characters have been selectively enhanced by past logging, which for economic reasons concentrated on individuals with regular crown and solid trunk.…”
Section: Stand Structure and Regenerationmentioning
confidence: 89%
“…The yew is considered as a slowly growing and long-living plant. In Great Britain it grows from 0.051 up to 5.5 mm/year in thickness (Moir, 1999), in Ireland -from 0.095 to 3.0 mm/ year, and in Denmark -from 1.4 to 2.6 mm/year (Thomas & Polwart, 2003). In Poland the average width of tree rings for the yew population amounts to 0.83 mm (from 0.27 up to 1.47 mm) (Cedro, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a number of authors suggest that the girth has only limited use in estimating the age of a yew tree (e.g. Denne 1987; Moir 1999) and should be interpreted with reference to soil type, history of the canopy, exposure, etc.…”
Section: Response To Environmentmentioning
confidence: 99%
“…High summer temperatures (particularly June) appeared to inhibit growth. Moir (1999) concluded that mild/wet winters combined with cool summers provide ideal growing conditions for yew, and that hot dry summers adversely affect yew growth. The yew chronology cross‐matched well with those of Pinus , Fagus , Castanea , Carya , and to a lesser extent Quercus .…”
Section: Structure and Physiologymentioning
confidence: 99%
See 1 more Smart Citation